10.1016/S0271-7964(09)79241-9 (CrossRef Listing of Deleted DOIs, 2000)
Background Medication adherence is poor among individuals with serious mental illness (SMI). Few studies demonstrated the effectiveness of remote medication dispensing and adherence monitoring interventions among individuals with SMI. Objective To understand medication dispensing rates associated with the use of remote medication dispensing and adherence monitoring device and identify associated demographic and clinical characteristics. Methods In this cohort study, individuals' characteristics were measured at the baseline and dispensing records were followed from their enrollment and subsequent device installation as early as January 2019 until June 2023. Individuals were eligible to participate if they were had a diagnosis of serious and persistent mental illness, age 18-64, were currently being prescribed psychiatric medications, and receiving mental health services from a participating community mental health agency (CMHA). Participants were recruited through a combination of self-selection and referrals from agency staff. Our intervention was the use of the remote medication dispensing and adherence monitoring device. Our measure was participants' daily medication dispensing. Results The final sample consisted of 99 participants. The mean age of the participants was 49 years (SD=12.08), with 64% identified as men, and 41% as Black/African American. The average dispensing rate was 92.9%, with 90 individuals having dispensing rates greater than 80%. The results of the hierarchical Bayesian logistic regression model showed that participants adhered better to evening doses compared to morning doses (IRR=1.11, 95% CI=1.06-1.16). Dispensing adherence was poorer on weekends compared to weekdays (IRR=0.87, 95% CI=0.83-0.91). For every additional year on using the device, the rate of adherence increased by 1% (IRR=1.01, 95% CI=1.00-1.01). The rate of dispensing dropped by 22% after the onset of the COVID-19 pandemic (IRR=0.78, 95% CI=0.71-0.86) and African Americans had a 29% lower rate of dispensing compared to whites (IRR = 0.71, 95% CI = 0.55-0.90). The rate of dispensing did not differ by age, sex, and educational attainment, or the level of sadness, emotional and behavioral dyscontrol, cognitive function or psychotic symptoms at the baseline. Conclusions The high adherence rate observed, regardless of baseline psychopathology levels, highlights the potential of remote medication dispensing and adherence monitoring devices to address adherence challenges in SMI populations. Observed variation in dispensing behavior by dose timing and contextual factors suggests opportunities for intervention, including aligning dosing schedules with patient routines, providing additional support during periods of disruption (e.g., weekends or major life events), and tailoring strategies to address disparities across patient groups. These findings highlight the role of targeted, context-aware approaches to improve adherence in community-based SMI care. The findings support the integration of digital adherence monitoring within mental health services, especially in settings where traditional adherence support may be challenging. Clinicaltrial nCT03775044.